PECULIARITIES OF USING MODERN METHODS OF TEACHING ENGLISH - Eldorbek Khamitov (European Science Publishing, 2024)
Teachers who have given clear directions only to have students raise their hands and ask, “Right, what do we do now?” know how important it is for tourism faculty students to learn how to listen and speak in their early years. Reading, writing, speaking, and listening all come together as kids get to know the English language and improve their speech skills. This piece talks about the problem of understanding what you hear as an important part of everyday communication. While listening is an important part of learning a language, it was not given much attention in traditional language classes for a long time. This piece shows how listening activities can greatly improve speaking skills by looking at both theoretical frameworks and real-world applications.
Keywords: Language learning, speaking skills, listening activities, language acquisition, communication proficiency.